Gearing up for the ASEAN Economic Community (AEC) integration 2015 a communication plan to create awareness of UP Mindanao students - Bernales, Mary Lyn E.
This thesis addresses the unfamiliarity of current UP Mindanao freshmen (incoming sophomores next year) regarding the ASEAN Integration and its changes. The need for thorough information dissemination was addressed through the development of a communication plan. The research part discusses the existing updates regarding the Integration?s changes. Also, it tackles the survey findings which concentrate on the respondents? demographics, their knowledge, and their attitude towards the integration. With the aid of Berger?s Planning theory, Rogers? Diffusion of Innovations Theory, and the ROPE process, the communication plan was produced based on the findings. The Planning theory served as an umbrella theory by highlighting communication as a goal-driven process. All communication efforts were driven by goals and objectives which were determined through formative evaluation. Meanwhile, the Diffusion of Innovations Theory was employed to proved that the respondents ( who presented the target audience) vary in their rate of adoption of an innovation. Thus, the respondents were segmented into different adopter categories in order to assess and address their respective communication needs. Using the findings, goals and objectives were set for the communication plan. Specific objectives were tailored for each adopter category. Moreover, communication gaps were identified, resulting to the development of key messages. Most messages pertained to the concepts of ASEAN, AUN, and the ASEAN Integration. Delivering such messages to the audience required various communication channels. Overall, the campaign is composed of a series of forums to inform, to educate, and to communicate with the audience. Supplementary tools included posters, infographics, brochures, leaflets, and the like. Evaluative methods were also determined by the researcher for the future monitoring of the campaign?s progress.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Speech/Corporate Communication